1996
DOI: 10.3189/s0022143000003531
|View full text |Cite
|
Sign up to set email alerts
|

Mass balance of White Glacier, Axel Heiberg Island, N.W.T., Canada, 1960–91

Abstract: ABSTRACT. While Glacier is a ya lley glac ier a t 79.5° N with a n area of 38.7 km 2 .Its m ass bala nce ha s b ee n meas ured , oyer 32 years with a 3 yea r gap, b y stand a rd tec hniques using th e slra ti g ra phi c sy ·te m wi th a stake den si l)' of th e order of onc sla ke p CI' km 2 . Errors in stak e m ass bala nce are abo ut ± (200-250 ) mm , du e larg ely to the local un represe n ta ti\'el1ess of measuremen ts. Errors in th e whole-gla cier mass balan ce B arc of the same order as sin gle-sla k e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…The thickness of superimposed ice was measured by drilling ice to the previous summer surface, which was determined by locating deposition of dark-colored surface dust. Uncertainties in the stake mass-balance measurements arise from stake readings and snow/ice density used for conversion from volume to mass (Cogley and others, 1996). The accuracy of stake reading was ±20 mm w.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of superimposed ice was measured by drilling ice to the previous summer surface, which was determined by locating deposition of dark-colored surface dust. Uncertainties in the stake mass-balance measurements arise from stake readings and snow/ice density used for conversion from volume to mass (Cogley and others, 1996). The accuracy of stake reading was ±20 mm w.e.…”
Section: Methodsmentioning
confidence: 99%
“…Following the values estimated by previous Greenland studies (±0.23 to ±0.28 m w.e.) (Bauer, 1961; Braithwaite, 1986; Cogley and others, 1996; Machguth and others, 2016), we assumed ±0.25 m w.e. as an uncertainty arising from the SMB inhomogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…in the Expedition Fiord region of Axel Heiberg Island, Nunavut. The mean annual temperature of the region is ~−20°C and mean precipitation at the highest elevations is ~370 mm a −1 , based upon a 41-year snow pit record of annual accumulation on Müller Ice Cap (Cogley and others, 1996). Since the onset of mass-balance observations in 1960, the mean decadal ELA has risen from 1000 m a.s.l.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Though great care was taken in field measurements, these are inevitably affected by large errors. Cogley and others (1996) concluded that errors in fieldwork are of the same order as errors in individual stake readings, and can eventually reach 0.25 mw.e.…”
Section: Mass-balance Methodsmentioning
confidence: 99%